Peningkatan Kepuasan Pelanggan Melalui Pengawasan Petugas TransJakarta - Asti Rahayu; Suripno Suripnob; Adenan Suhalis; Prasadja Ricardianto; Peppy Fachrial (Institut Transportasi dan Logistik Trisakti, 2022)
TransJakarta service transportation is an affordable mass transportation services that implements Bus Rapid Transit system in the Jakarta. TransJakarta has implemented minimum service standards as requirement for providing public transportation services with buy the service scheme. By implementing minimum service standard, its expected to increase customer satisfaction, but several media and other research have found that customer satisfaction isn’t optimal due to various factors such as lack of comfort, lane disturbances that affect travel speed, need some additional facilities at the bus stop and long waiting time at rush hours. This study aims to see the effect of TransJakarta service quality on increasing customer satisfaction by mediating officer supervision. This research was conducted by survey of 40 TransJakarta customer respondents on Corridor I Blok M-Kota route in 2021, and analyzed using Path analysis. The results showed that the service quality of TransJakarta has positive and significant effect on customer satisfaction. Officer supervision in TransJakarta services has positive and significant direct effect on customer satisfaction. Officer supervision in providing TransJakarta services has positive and significant direct effect on service quality. Meanwhile, TransJakarta qulity service indirectly has a positive but not significant effect on customer satisfaction by mediating the officer supervision.